2005
DOI: 10.1097/01.jcp.0000168879.03169.ce
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Antidepressant Response in Recent Antidepressant Clinical Trials

Abstract: Some previous reports suggest that women respond differently than men to antidepressant treatment. Much of this literature compares men and women's response to tricyclics to that of newer antidepressants (SSRIs, SNRI), or only examines one particular antidepressant. This study compares men and women's responses to 6 newer antidepressants. A total of 15 randomized, placebo-controlled trials that included 323 depressed patients were examined for sex differences in antidepressant treatment response. Women had a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
1
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(145 citation statements)
references
References 22 publications
6
132
1
6
Order By: Relevance
“…Of the published peer-reviewed studies, five found no difference in the efficacy of SSRIs in men and women (25)(26)(27)(28)(29), and six found SSRIs to be more effective in women (30)(31)(32)(33)(34)(35). There are no reports of SSRIs being more effective in men.…”
Section: Significancementioning
confidence: 92%
“…Of the published peer-reviewed studies, five found no difference in the efficacy of SSRIs in men and women (25)(26)(27)(28)(29), and six found SSRIs to be more effective in women (30)(31)(32)(33)(34)(35). There are no reports of SSRIs being more effective in men.…”
Section: Significancementioning
confidence: 92%
“…Together, these observations suggest the potential importance of considering the role of sex and the ovarian steroid milieu in evaluating the efficacy of antidepressant therapy. Indeed, several studies have reported that women respond better to selective 5-HT re-uptake inhibitors (SSRI) than men (Kornstein et al, 2000;Joyce et al, 2003;Khan et al, 2005). Animal models of depression are usually based on the reproduction of one or a few depressive symptoms (e.g.…”
Section: Sex Differences In Animal Models Of Depressionmentioning
confidence: 99%
“…MDD symptoms are characterized by overall emotion dysregulation, low mood, anhedonia, and poor affect, among others [3]. Current treatments are only effective at inducing remission in a portion of the population [4], and men and women respond differently to pharmacological treatment [5]. Cross-cultural epidemiological studies that control for reporting biases have found that depression affects women at twice the rate that it affects men.…”
Section: Introductionmentioning
confidence: 99%